Peningkatan Kemampuan Motorik Kasar Melalui Permainan Estafet Bola Bambu pada Anak Kelompok B di TK Dharma Wanita Sumengko Kwadungan Ngawi - Fitriana, Nur; Wijayanti, Arwendis; Dwi tanto, Octavian (UIN Raden Mas Said Surakarta, 2023)
This purpose of this research on to find out whether the estafet bola bambu dan improve children's gross motor skills and to find out how estafet bola bambu Van improve children's gross motor skills at Dharma Wanita Sumengko kindergarten in 2022-2023. The subject of this research is 8 children. This research method ia action research which refers to the class action research of Kemmis and Mc. Taggart which includes four stages: planning, action, observation, and reflection. This study consisted of two cycles, each cycle consisting of 3 meetings. Data analysis techniques used on this. Study are qualitative and quantitative analysis. Qualitative data analysis by analyzing data from interviews during the study for data reduction, data display, and data verification steps. Quantitative data analysis with descriptive statistic comparing the results obtained from pre-cycle, cycle 1, and cycle 2. This result of this study indicate an increase in children's grass motor skills thought estafet bola bambu.